Intelligent IEEE 802.11B Wireless Networks Mac Layer Diagnostic Controller in Mobile Ad Hoc Network - Soo, Wooi King; Phang, Keat Keong; Ling, Teck Chaw; Ang, Tan Fong (Malaysian Journal of Computer Science, 2007)
In a mobile ad hoc network (MANET), when a node fails during the RTS-CTS handshake process, the MAC protocol is able to identify whether the failure was caused by link failure or due to congestion by inspecting the recorded radio signal strengths. If the cause is due to actual link failure, then MAC abandons any further attempt to retry communicating with the node. If the failure is due to congestion, the conventional approach in attempt to reconnect the link is wasteful of both time and bandwidth. This will in turn cause packet loss and hence degradation in the TCP performance. In this paper, an intelligent link diagnostic controller for IEEE 802.11b wireless network is proposed. The proposed mechanism incorporates fuzzy controller in the MAC protocol of a node to diagnose the link based on the distances and relative velocities before the attempt to reconnect is made. The incorporated intelligence allows a node to adjust the number of retry in proportional to the probability of getting the node connected. Simulation results show that the proposed fuzzy approach increases the amount of TCP packets transferred whilst reducing the number of TCP packets dropped and maintaining the level of overhead traffic. This mechanism improves the TCP performance by7% on average.